Application of H-Point Standard Addition Method in Kinetic-Spectrophotometric Determination of Phenylephrine in Nasal Drops and Tetracycline in Capsule - Faeza H. Zankanah (Journal of Global Pharma Technology, 2016)
A new simultaneous spectrophotometric-kinetic method was developed to determine phenylephrine (PHEN) and tetracycline (TETR) via H-point standard addition method (HPSAM). The proposed procedures rely on the measurements of the difference in the rate of charge-transfer (CT) reaction between each of PHEN and TETR as electron donors with p-Bromanil (p-Br) as an electron acceptor. Different experimental factors which affect the extent of the complex formation were investigated by monitoring the value of absorbance at 446 nm. Time pair of 50 -100 sec was selected and employed, among different examined pairs since it results in the highest accuracy for HPSAM-plot. Linear calibration graphs in the concentration ranges of 10.0-40.0 and 10.0–50.0 mg/L were obtained for PHEN and TETR, respectively and the proposed method was applied successfully in the determination of PHEN and TETR in their pure form and in commercial formulations.Keywords: Spectrophotometry, Kinetic H-point standard addition method, Phenylephrine, Tetracycline, Simultaneous analysis.